2019
DOI: 10.3892/ijmm.2019.4194
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-302e attenuates inflammation in infantile pneumonia though the RelA/BRD4/NF-κB signaling pathway

Abstract: In the present study, the main focus was investigating the role of microRNA (miRNA)-302e in infantile pneumonia (IP) and exploring the potential protective mechanisms. Briefly, the expression of miRNA-302e was reduced in a mouse model of IP. In addition, the administration of anti-miRNA-302e increased inflammation and induced the protein expression of RelA, bromodomain-containing protein 4 (BRD4) and nuclear factor (NF)-κB in the in vitro model of IP. In contrast, over-expression of miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…BRD4 is just like a dancer on the stage of inflammation, and is functionally required for inflammatory gene regulatory network depended on NF κB signal ( 36 ). It was demonstrated that miRNA302e attenuated inflammation in infantile pneumonia through the RelA/BRD4/NF κB signaling pathway ( 37 ). In addition, infection of respiratory syncytial virus induced airway inflammation through the coupling between BRD4 and NF κB ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…BRD4 is just like a dancer on the stage of inflammation, and is functionally required for inflammatory gene regulatory network depended on NF κB signal ( 36 ). It was demonstrated that miRNA302e attenuated inflammation in infantile pneumonia through the RelA/BRD4/NF κB signaling pathway ( 37 ). In addition, infection of respiratory syncytial virus induced airway inflammation through the coupling between BRD4 and NF κB ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-218-5p, miR-29a, miR-29b, and miRNA-302e inhibit BRD4 expression in activated human pulmonary microvascular endothelial cells, primary hepatic stellate cells, human bronchial epithelial cells, and A549 cells, respectively. 30 , 42 , 43 We still need to clarify the TFs responsible for BRD4 expression in innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, miRNAs are associated with various diseases, including cancer (8) and viral infections (9), and have been identified as biomarkers for pneumonia (10). Moreover, numerous miRNAs are involved in the progression of pneumonia; miR-302e reduced inflammation during infantile pneumonia via the NF-κB signaling pathway (11), miR-146a-5p regulated lipopolysaccharide (LPS)-induced cell apoptosis and inflammation via CC motif chemokine ligand 5 during acute pneumonia (12), and miR-370-3p modulated LPS-induced cell apoptosis and inflammation via toll like receptor 4 during acute pneumonia (13). It has also been reported that miR-127 may reduce lung inflammation by targeting immunoglobulin (Ig) G Fcγ receptor I (14).…”
Section: Introductionmentioning
confidence: 99%